Factors of visual organization effective on the protection of vernacular landscapes in the foothill villages - Asadpour, Faezeh; Mahdinejad, Jamal-e-Din; Sharghi, Ali; Saleh Sedghpour, Bahram (Journal of Environmental Engineering and Landscape Management, 2025)
As the cultural heritage of a country, the texture of vernacular villages is the main factor that forms the vernacular landscape. These textures provide visual values that play a determinant role in presence and residence continuity in rural areas. However, many vernacular landscapes of foothill villages in Iran have become problematic due to interferences and a lack of proper management mechanisms. It is essential to formulate a theoretical framework for parameters affecting the vernacular landscape protection to handle the development process and preserve this precious heritage. This is an exploratory study in terms of nature and is descriptive-survey research in terms of data collecting method. The statistical population comprises 31 experts in architectural and rural fields who were interviewed through a non-random network method. The techniques used in this study include content analysis, Delphi, and correlation, and the collected data are analyzed using SPSS software through Q factor analysis, Pearson correlation, and regression analysis. The results show that 9 factors can be extracted based on the priorities and mental patterns of the experts for visual organization: adaptability, coordination and orderliness, visibility, comfort, permeability, compatibility, legibility, attractiveness, and landscape. Among the mentioned factors, the higher explained variance percentage (14.097%) belongs to adaptability. According to the obtained results, 99.4% of variations in the vernacular landscape have been explained by these 9 factors among which, visual attractiveness and visibility have the highest effect on vernacular landscape protection in foothill villages with impact coefficients of 0.318 and 0.279, respectively at the significance level of 99%.